2017
DOI: 10.1093/fampra/cmx034
|View full text |Cite
|
Sign up to set email alerts
|

Adverse impacts of chronic pain on health-related quality of life, work productivity, depression and anxiety in a community-based study

Abstract: Chronic pain, particularly multisite pain and neuropathic pain, significantly affected physical and psychological health. Chronic pain is a multifaceted health condition that requires a multidisciplinary treatment approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
2
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(121 citation statements)
references
References 19 publications
2
87
2
7
Order By: Relevance
“…Our findings also showed that pain-related hindrance to ADLs was significantly associated with negative impact on patients' work performance and assurance of job security. The impact of chronic pain on the biopsychosocial effects of patients is well-established [41][42][43][44]. Therefore, physicians are encouraged to adopt the biopsychosocial model to assess and treat CNCP [16,45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also showed that pain-related hindrance to ADLs was significantly associated with negative impact on patients' work performance and assurance of job security. The impact of chronic pain on the biopsychosocial effects of patients is well-established [41][42][43][44]. Therefore, physicians are encouraged to adopt the biopsychosocial model to assess and treat CNCP [16,45,46].…”
Section: Discussionmentioning
confidence: 99%
“…The Centers for Disease Control and Prevention (CDC) estimated that 20% of adults in the United States were affected by chronic pain in 2016, which translates to about 50 million Americans, and the World Health Organization has reported worldwide estimates of prevalence to range from 5% to 33%, with an average of 21.5% . Surveys have found that patients with chronic pain often report incomplete pain relief from available treatments, and a significant proportion of patients report impacts on their general activity, mood, and enjoyment of life, as well as their ability to walk, work, or sleep …”
Section: Introductionmentioning
confidence: 99%
“…3 Surveys have found that patients with chronic pain often report incomplete pain relief from available treatments, and a significant proportion of patients report impacts on their general activity, mood, and enjoyment of life, as well as their ability to walk, work, or sleep. 4,5 Because of the ubiquity of chronic pain in our society, safe and effective treatments are needed in order to manage these conditions. There are several interventions available for treating chronic pain, including nerve blocks, surgeries, implantable drug delivery systems, and nerve stimulators; however, the first line of treatment for pain is most often oral analgesics, including acetaminophen, nonsteroidal anti-inflammatory drugs (NSAIDs), and opioids.…”
Section: Introductionmentioning
confidence: 99%
“…Negative effects on the quality of life of almost all types of pain with or without (such as arthritis, neuropathic, somatic, psychogenic or visceral) malignancy have been demonstrated. 13,14 The relationship between duration of the pain and the quality of life When the quality of life of patients with acute pain and chronic pain was compared, patients with chronic pain had lower scores in all dimensions of quality of life compared to those who suffered from acute pain or had no pain. 15,16 The relationship between severity of the pain and the quality of life There is a dose-response relationship between pain and quality of life; one increases, the other decreases proportionally.…”
Section: The Relationship Between the Type Of Pain And The Quality Ofmentioning
confidence: 99%